Analysis of stray flux spectral components in induction machines under rotor bar breakages at various locations - Panagiotou, P. A.; Arvanitakis, I.; Lophitis, Neophytos; Antonino-Daviu, J. A.; Gyftakis, K. N. (My University, 2018)
Induction machines under rotor electrical faults have been subjected to intensive research over the years. It is not only the nature of the fault that makes it important to study, but also the differences observed regarding this fault's effect on the motor's conditions. One of these conditions is the rotor bar breakages at non adjacent positions, which has drawn the attention of researchers due to the false negative diagnostic alarms that may be caused. In this paper, a novel approach is presented aiming to reliably detect this type of fault condition. The proposed method is based on the analysis of specific subcomponents of the stray flux over time. The analysis is implemented on an industrial 1.1 MW industrial induction motor, since large industrial motors make the cases where MCSA might fail due to the weak speed ripple effect and closeness of the fault's sidebands to the fundamental harmonic. The work has been carried out with extensive Finite Element simulations.
Keywords: Broken bars; Induction motor; Signal processing; Spectral content; Stray flux